الاعتداء على المال العام في ليبيا باستغلال النفوذ : دراسة فقهية تحليلية - قماطي٬ الرابيع محمد منصف (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
The research aims to shed light on the issue of violation of public fund in Libya through exploitation in spending public fund from the both the perspectives of Islamic jurisprudence and common law. It also highlights the standard which distinguishes between public fund and others and its limitations in expenditure according to the common law and Islamic through the legal provisions for protection of the public and to enhance the proper expenditure of the public fund and prevent wastage. This study also entails the right of the state and individuals in public fund to achieve a responsible public spending. It also makes reference to crimes that affect public property and justice. The study also explicates the general fund related to crimes that have affected expenditure growth and governance. Libya has witnessed many corruption cases on public funds during the period of the former regime which necessitated discussion about the magnitude of these violations and its danger to the Libyan society. This study employed the inductive, analytical and critical approach with the addition of the quantitative method used to demonstrate important statistical data of the research. This research found that exploitation spending is a means of financial corruption and it a risk that leads to violation of the public interest administration. Therefore, it is possible to employ jurisprudential rules in the application of justice and proper controls in the preservation of public money by referencing to the Shariah and arbitration in every domain of human endeavor. The researcher concluded this research with a set of recommendations